Transformational Leadership in Christian Religious Eduction: Ethics and the Future of Humanity - Tri Subekti; Sarah Wassar (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
This study explores the role of transformational leadership within the context of Christian Religious Education, emphasizing its ethical foundation and implications for shaping the future of humanity. In an era marked by moral ambiguity, rapid technological progress, and declining spiritual values, Christian education faces the urgent challenge of cultivating ethical character, spiritual maturity, and social responsibility. The problem addressed in this research is the gap between leadership practices in Christian educational settings and the transformative outcomes expected in students’ moral and spiritual development. The objective of this study is to analyze how transformational leadership can be effectively applied to Christian Religious Education to foster ethical behavior and visionary thinking. Using a qualitative descriptive method supported by literature analysis and interviews with Christian educators and leaders, this research identifies core principles and strategies that align biblical teachings with transformational leadership theory. The findings reveal that transformational leaders who model Christ-centered values, inspire through vision, and mentor with compassion significantly impact learners’ ethical formation and worldview. The synthesis of ideas highlights the integration of faith, leadership, and pedagogy as a holistic approach to addressing the ethical and existential challenges of the 21st century. In conclusion, transformational leadership within Christian Religious Education is essential in guiding learners toward a life of purpose, integrity, and contribution to a humane and spiritually grounded society.